2016
DOI: 10.4048/jbc.2016.19.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Pneumonitis in Association with Internal Mammary Node Irradiation in Breast Cancer Patients: An Ancillary Result from the KROG 08-06 Study

Abstract: PurposeThe aim of this study is to present the incidence of radiation pneumonitis (RP) reported within 6 months after treatment for breast cancer with or without internal mammary node irradiation (IMNI).MethodsIn the Korean Radiation Oncology Group (KROG) 08-06 phase III randomized trial, patients who were node-positive after surgery were randomly assigned to receive radiotherapy either with or without IMNI. A total of 747 patients were enrolled, and three-dimensional treatment planning with computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
(29 reference statements)
1
25
0
Order By: Relevance
“…Thus, the role of IMN irradiation in patients with positive axillary lymph nodes remains controversial. Choi et al 21 reported that SRP occurred in 6.5% of patients who underwent IMN irradiation and in 3.3% of patients without IMN irradiation ( p = 0.047) and considered that IMN irradiation resulted in increased radiation exposure to the lung and a higher risk of developing SRP. Therefore, it is important to carefully select patients for treatment with IMN irradiation and adopt more accurate radiotherapy technology in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the role of IMN irradiation in patients with positive axillary lymph nodes remains controversial. Choi et al 21 reported that SRP occurred in 6.5% of patients who underwent IMN irradiation and in 3.3% of patients without IMN irradiation ( p = 0.047) and considered that IMN irradiation resulted in increased radiation exposure to the lung and a higher risk of developing SRP. Therefore, it is important to carefully select patients for treatment with IMN irradiation and adopt more accurate radiotherapy technology in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, changes to the guidelines did not eliminate the controversies regarding irradiation of the internal mammary lymphatic chain. The reason was probably that the recurrence rate was only 2% according to clinical reports [13], and the irradiation dose of cardiopulmonary was increased by irradiation of the internal mammary lymphatic chain [14,15]. In this study, we retrospectively examined data from 114 patients with local and/or regional lymph node recurrence without adjuvant radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the guidelines did not eliminate the controversies of irradiation of internal mammary lymphatic chain. The reason was probably that the recurrence rate was only 2% according to clinical reports [13], and the irradiation dose of cardiopulmonary was increased by irradiation of the internal mammary lymphatic chain [14,15]. We studied 114 patients of local and/or regional lymph node recurrence without adjuvant radiotherapy retrospectively.…”
Section: Discussionmentioning
confidence: 99%